2019
DOI: 10.1093/hmg/ddz123
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mTORC1 inhibition rescues behavioral and biochemical deficits resulting from neuronal Depdc5 loss in mice

Abstract: DEPDC5 is now recognized as one of the genes most often implicated in familial/inherited focal epilepsy and brain malformations. Individuals with pathogenic variants in DEPDC5 are at risk for epilepsy, associated neuropsychiatric comorbidities and sudden unexplained death in epilepsy. Depdc5flox/flox-Syn1Cre (Depdc5cc+) neuronal-specific Depdc5 knockout mice exhibit seizures and neuronal mTORC1 hyperactivation. It is not known if Depdc5cc+ mice have a hyperactivity/anxiety phenotype, die early from terminal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 47 publications
0
31
0
2
Order By: Relevance
“…When treated with rapamycin (50 nM) or torin1 (50 nM) for 24 hours, these N2aC showed a reduction in soma diameter (Fig. 2C,D) equivalent to WT cell diameter (p<0.001) demonstrating that Nprl3 loss resulted in mTOR-dependent soma enlargement 14,15 .…”
Section: Cell Soma Diametermentioning
confidence: 88%
See 2 more Smart Citations
“…When treated with rapamycin (50 nM) or torin1 (50 nM) for 24 hours, these N2aC showed a reduction in soma diameter (Fig. 2C,D) equivalent to WT cell diameter (p<0.001) demonstrating that Nprl3 loss resulted in mTOR-dependent soma enlargement 14,15 .…”
Section: Cell Soma Diametermentioning
confidence: 88%
“…In our study, CRISPR/Cas9 KO of Nprl3 resulted in persistent and inappropriate localization of mTOR to the lysosomal membrane during amino acid starvation. Indeed, loss of Depdc5 in mouse renders GATOR1 non-functional 14 and previous studies have shown that shRNA mediated knockdown of Depdc5 or Nprl3 resulted in increased localization of mTOR to the lysosomal surface even during amino acid starvation 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein encoded by Cdh2, N-cadherin, is involved in ALI and pulmonary fibrosis. 38 Some studies have shown that Nprl3 (GATOR1 complex subunit) participates in the pathogenesis of sepsis and mediates the expression of many inflammatory factors via the mammalian target of rapamycin (mTOR) pathway, [39][40][41] suggesting that Nprl3 contributes to sepsis-induced ALI, perhaps through a regulatory interaction with mmu_circ_0001679 or mmu_circ_0001212.…”
Section: Verification Of Dysregulated Circrnas and Mrnasmentioning
confidence: 99%
“…Upon amino acid starvation, KLHL22 is bound and trapped by 14-3-3 proteins in the nucleus, resulting in a dramatic increase in DEPDC5 protein stability 26 . Interestingly, depletion of DEPDC5 results in the decreased expression of the other two GATOR1 components NPRL2 and NPRL3 23 , 27 . We reasoned that under amino acid starvation the expression levels of Nprl2 and Nprl3 might also be regulated, especially in the invertebrates that have no orthologs of KICSTOR and CASTOR1.…”
Section: Introductionmentioning
confidence: 99%